2010
DOI: 10.1161/circulationaha.109.908988
|View full text |Cite|
|
Sign up to set email alerts
|

Homoarginine, Cardiovascular Risk, and Mortality

Abstract: Background-Homoarginine is an amino acid derivative that may increase nitric oxide availability and enhance endothelial function. The effect of the level of homoarginine on cardiovascular outcome and mortality is unknown. Methods and Results-We assessed cardiovascular and all-cause mortality according to homoarginine levels in a cohort of 3305 subjects referred for coronary angiography from the LUdwigshafen RIsk and Cardiovascular Health (LURIC) Study. After investigating the relation of homoarginine with kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
133
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(147 citation statements)
references
References 28 publications
11
133
1
2
Order By: Relevance
“…Elevated plasma a-aminoadipic acid and homoarginine, two metabolites of L-Lys, in group Lys indicated that the rats in group Lys had increased intestinal absorption of L-Lys. [23][24][25] However, the elevation of plasma Lys in group Lys was not statistically significant. As far as we examined, plasma Ala, Pro, Arg, Gln, Asn, homoarginine, and a-aminoadipic acid in group Lys seemed to play some roles in the suppression of vascular calcification.…”
Section: L-ly Protected the Femora From Osteoporotic Changes In Adenimentioning
confidence: 74%
See 2 more Smart Citations
“…Elevated plasma a-aminoadipic acid and homoarginine, two metabolites of L-Lys, in group Lys indicated that the rats in group Lys had increased intestinal absorption of L-Lys. [23][24][25] However, the elevation of plasma Lys in group Lys was not statistically significant. As far as we examined, plasma Ala, Pro, Arg, Gln, Asn, homoarginine, and a-aminoadipic acid in group Lys seemed to play some roles in the suppression of vascular calcification.…”
Section: L-ly Protected the Femora From Osteoporotic Changes In Adenimentioning
confidence: 74%
“…23,44 The causal relationship between low homoarginine and an increased incidence of cardiovascular events has been mainly attributed to suppressed nitric oxide (NO), because homoarginine induces NO by two pathways: (1) homoarginine itself serves as a substrate for NO synthase; and (2) homoarginine inhibits arginase and thereby increases arginine, a major substrate for NO synthase. 23 In addition to the property of homoarginine as an inducer of NO, our current study revealed that homoarginine works as an inhibitor of mineral precipitations ( Figure 8A). The property of homoarginine as an inhibitor of arginase seems to explain the reason, at least in part, why plasma Arg, another precipitate-inhibitory amino acid, was elevated in group Lys ( Figure 8A, Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potentially more important role that has received some attention is in the inhibition of the enzyme arginase with consequent preservation of arginine for NOS [24]. Indeed, low homoarginine concentrations have been recently shown to be associated with mortality and cardiovascular events [25]. Furthermore, increased homoarginine concentrations during normal pregnancy are associated with increases in brachial artery diameter and flow-mediated dilatation [26].…”
Section: Discussionmentioning
confidence: 99%
“…26 Such a role of L-homoarginine in endothelial function is supported by the findings of a study in patients undergoing coronary angiography or maintenance hemodialysis, where a low serum level of L-homoarginine was a strong predictor of subsequent mortality. 53 Homoarginine may also inhibit platelet aggregation and stimulate insulin secretion, 54 --56 actions, which affect cardiovascular health and may have a role in PE.…”
Section: Discussionmentioning
confidence: 99%